Вы находитесь на странице: 1из 13

11

6.



dx
dt = a11 x + a12 y
(1)

dy
=a x+a y
21
22
dt
x = y = 0 .
:

a11
a21

a12
=0
a22

2 ( a11 + a22 ) + ( a11a22 a12 a21 ) 2 Tr A + det A = 0


.
1)
.
(1)
x = C1e1t ,

x
y = C2 e2t , t = ln
1 C1
1

x 1
y = C2 .
C1
2

> 0,

x 1
)
1 < 2 < 0 , x = C1e1t 0, y = C2 e2t 0, y = C2
t +
t +
C1
x = y = 0 .
)

0 < 1 < 2 , x = C1e1t ,


t +

y = C2e2t ,
t +

x
y = C2
C1

2
<1
1

> 0, 2 >1
1
1

x = y = 0 .
2

1 < 0 < 2 , x = C1e

1t

0,

t +

y = C2 e

2t

t +

x 1
y = C2
C1

( <0)

x = y = 0 .
(1) .

1 = + i , 2 = i .
2)
(1)
x2 y 2
x = C1e t cos t , y = C2 e t sin t
+ 2 = e 2 t .
2
C1 C2
)
< 0 , x = y = 0
.
)
> 0 , x = y = 0 .
)
= 0 , x = y = 0 , .
(1) .

1 = 2 = .


3)
(1)
x = C1et ,

y = C2 e t

C2
x.
C1

y=

)
< 0 , x = y = 0
.
)
> 0 , x = y = 0
.

4)
(1) :
x = C1et ,

y = ( C2 + C1t ) et ,

< 0 ,

1 = 2 = .

x
C x x

ln
y = C2 + 1 ln
C1
C1 C1

x = y = 0

t=

.
)
> 0 ,
.

x = y = 0

(1) .

..

5)
1 0,

x = C1e1t , y = C2 .
7.

2 = 0 . (1)

( )

x = f ( x) ,
f ( x ) - C (a, b) .

(1)

U ( x ) = f ( )d ,

c ( a, b )

(2)

.
(1)

x= p

p = f ( x ) = U ( x )

(3)

f ( x ) , ,
(3).
x = x0 (1) x = x0 , p = 0
(3). x = x0 (1)
U ( x) . , x = x0 ,
f ( x0 ) = 0 , (2), U ( x0 ) f ( x0 ) = 0 .
, x0 U ( x) ,
.
.
f ( x ) - C 2 (a, b) . ,
1) x = x0 - U ( x) ,

x = x0 , p = 0 (3) ;
2) x = x0 - U ( x)
x = x0 , p = 0 (3) .
.
x0 = 0 ,
y = x x0 .
x = 0 - ,
U ( x) > U (0) x 0 .

f ( x0 ) > 0 ,

p2
V ( x, p ) = U ( x ) U ( 0 ) +
2
- .
V
V
p+
( U ( x ) ) = 0 ,
x
p
, , x = x0 , p = 0
.
x = 0 - U ( x) f (0) > 0 ,
U (0) = 0 , U (0) = f (0) < 0
1
1
U ( x ) = U ( 0 ) + U ( 0 ) x + U ( x ) x 2 = U ( 0 ) x f ( x ) x 2 ,
0 < < 1.
N


2
2


=0
f ( x )

F ( x)

(3)

p = U ( 0 ) x + F ( x ) ,

x = p,

(4)

1
f ( x ) x 2 , x F ( x) Mx 2 .
2
(4):

F ( x ) =

p = U ( 0 ) x .

x = p,

1
0
A=

U
(0)
0

= U (0) , .

, ,

x = 0, p = 0 .
.
3. ,
, f ( x ) - C1 (a, b) . ,
.
8.

2-
.

10.

x = f ( x)

() :

(1)

x = p,
p = f ( x ) = U ( x )

(2)

p = 0
f (x ) = 0 .

f (x ) = 0

x =x ,
0
i

i = 1,2,..., n .

(x , 0)
0
i

(3)
( x , p )

(2). , (3)
, .. fx ( x i0 ) 0,
i = 1, 2,..., n .
,
. ,
.

. (1) .
, ,
(1)
(1) ( (2)).
20.

.
x = xi0 f ( x )

f (x ) = f ( x i0 ) + fx ( x i0 )( x x i0 ) + ( x x i0 ) .
N
=0

(2)

x = p,

.
x x i0 = x .

p = f x ( xi0 )( x xi0 )

( x , p )

( x, p ) = ( x , 0 ) ( x , p ) = ( 0, 0 )
0
i

x = p,

p = fx ( x i0 ) x .

1
= 2 fx ( x i0 ) = 0

1,2 = fx ( x i0 ) .
0
fx ( x i )
fx ( x i0 ) > 0 , ,

fx ( x i0 ) < 0 , .
,
(2) . .
1,2
, 1,2 - .
(2) (1).
30.

p > 0 (2), , , (1)


,
dp f (x )
=
(4)
dx
p

(4) pdp = f (x )dx ,


p2
= f (x )dx + C

p = 2 f (x )dx + C .
2
, p < 0 ,
p = 2 f (x )dx + C .

C
, ,
,
x .
(4), , .
, ,
( x 0, 0 ) , , t +
t .
, ( x 0, 0 ) ,

p = 2 f (s )ds .

(5)

x0

, (1)
, ( x 0 , p 0 )
, , (1) .
,
, , .
t + t .
,
t , .
40.

1.

.
d 2x
= x (a x ) f ( x ) , a > 0 .

dt 2
1- :

x = p,

p = x (a x)

(6)

x1 = 0, x2 = a f ( x ) = 0 (6)
( x , p ) = ( 0, 0 ) ( x , p ) = (a, 0 ) . , fx ( 0 ) = a > 0 ; fx (a ) = a < 0 , ( 0, 0 ) -
- , (a, 0 ) - - .
(6). . 3,
p2
= x (x a )dx + C = U (x ) + C ,
2
x3
x2
U (x ) =
a .

3
2

p = 2 x (x a )dx + C = 2U (x ) + C .

(7)

f ( x ) C ,
(6) 1- 3.

f(x)

. 1

3a
2

S1
a

p2
=
2

(x ) d x

S2

+C

. 2
3a
2
a

p
. 3
3a
2
a

1 f ( x ) .
2 f ( x ) :
p2
= f (x )dx + C = U (x ) + C .
2
, .
f ( x ) ,
1. f ( x )
p2
f ( x ) > 0 f ( x ) < 0 . x
2
, f ( x ) > 0 . x = a f ( x )
p2
, ..
.
2

p2

2

S1 S 2 , U ( x ) =
x = x

3a
0 x (a x )dx = a x (a x )dx , 0 x (a x ) dx = 0 . x = 2 .

x

x

p2

x ,
2
.
x
p2
= f (x )ds
x
2
0
f ( x ) < 0 , , U (x ) =

p2
2

x .
3 (0, 0) .
(.3) , , .
t .
dx
, : p =
> 0 , x
dt
, .. .
C . C ( )
2 ( ). (7)
, , x .
C 2
( ). (7)
, C (a, 0 ) .
.
. 3 (7) .
x 0
d 2x
= x (a x ) , x ( 0 ) = x 0 , x ( ) = 0 .
2
dt
.
. 30, , ( 0, 0 ) ,
t + , t .
x 0 , , ,
( 0, 0 ) .
.

(x 0, p ( 0) )
. , ( x 0 , p ( 0 ) )

x ( 0 ) = z ( 0 ) ,

t + , ( 0, 0 ) t + .
3a
3a
x 0 < 0 x 0 =
. 0 < x 0 <
,
2
2
, x 0 , ,
p ( 0 ) , ( x 0 , p ( 0 ) ) , ,
3a
( 0, 0 ) . p 0 >
, , .
2

2.
.
f ( x ) .

- .

d 2x
= f (x ) x ( x 2 a 2 ) .
dt 2
:
f (x ) = 0
x (x 2 a 2 ) = 0

x = 0, x = a .

f(x)
.4

S1
S1

S1
S1

-a

.5

p2
2

-a

.6
p

1
-a

.4 f (x ) = x ( x 2 a 2 ) .

fx x = 0, x = a : fx ( 0 ) < 0 , fx ( a ) > 0 . , 5,
( 0, 0 ) - , (a, 0 ) ( a, 0 ) - .
x

2
p2
x4
2 x
= f (x )dx =
a
+ C (. 5). ,

2
4
2
a
f ( x ) - , - ,
.

f (s ) ds =
a

f (s ) ds , (a, 0 )

( a, 0 )

p = 2 f (x )ds .
a

6 . 1 2
. , 1 2
.
C . C
OY .
(.6, ).
C ,
x2
OY , U ( x ) =

2
(.5, ). a < x < a C
, x > a -
(.6, ).
C
p2
U (x ) =
x .
2
C , 6
.
)

.

d 2x
= f (x ) x ( x + a1 )( x a2 ) ,
0 < a 2 < a1 .
dt 2
:
x = 0, x = a1, x = a 2 .

7 f (x ) = x ( x + a1 )( x a2 ) .
fx x , :
fx ( 0 ) < 0, fx ( a1 ) > 0, fx (a2 ) > 0 . , ( 0, 0 ) - ,

( a1, 0 ) (a2, 0 )

- .

p2
= f (x )dx + C .
2
C > 0 OY ( ).
C , .
x
p2

= f (s )ds . OY
2 a2
8

(a2, 0 ) .

(.9) (a2 , 0 ) .
x

(a1 , 0) p = 2 f (s ) ds
a1

(.9) .

f(x)
.7

S1
S1

S2
S2

-1

.8

p2
2

-1

.9
p

3.
.
:
d 2x
= f (x ) sin x .
dt 2
1-

x = p,
p = sin x .
x = m
f ( x ) = 0
1, m = 2k
,

fx ( m ) =
, k Z ,
,
(x m , p ) = ( m, 0 ) .
1, m = 2k + 1
(x 2k +1, p ) = ( (2k + 1) , 0 ) - , (x 2k , p ) = ( 2k , 0 ) - .
:
p2
= sin xdx + C = cos x + C .
2
U (x ) = cos x , ,
p = 2 cos x + C ,
C 2 .

10.

. 10
C = 2 , . 2 < C < 2 ,
(
, ). C > 2
,
( ),
.

.
(0, 0)
1) ;
x
2) , V (x , p) = 4 sin2 + p 2 .
2

Оценить